The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcell.2022.1009776
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic chromosome dynamics and double strand break formation in reptiles

Abstract: During meiotic prophase I, tightly regulated processes take place, from pairing and synapsis of homologous chromosomes to recombination, which are essential for the generation of genetically variable haploid gametes. These processes have canonical meiotic features conserved across different phylogenetic groups. However, the dynamics of meiotic prophase I in non-mammalian vertebrates are poorly known. Here, we compare four species from Sauropsida to understand the regulation of meiotic prophase I in reptiles: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 85 publications
4
8
0
Order By: Relevance
“…This is what we observed in the third marsupial species analyzed in this study, M. eugenii, which mimics the pattern described in mouse. Considering the phylogenetic relationships between the marsupials studied here (Figure 1) (Duchêne et al, 2017), and previous reports in other vertebrates (Blokhina et al, 2019;Marín-Gual et al, 2022a), the most parsimonious explanation is that bouquet polarization is an ancestral character in marsupials, and most probably in all vertebrates.…”
Section: The Conspicuous Bouquet Conformation Could Be An Ancient Fea...supporting
confidence: 66%
See 2 more Smart Citations
“…This is what we observed in the third marsupial species analyzed in this study, M. eugenii, which mimics the pattern described in mouse. Considering the phylogenetic relationships between the marsupials studied here (Figure 1) (Duchêne et al, 2017), and previous reports in other vertebrates (Blokhina et al, 2019;Marín-Gual et al, 2022a), the most parsimonious explanation is that bouquet polarization is an ancestral character in marsupials, and most probably in all vertebrates.…”
Section: The Conspicuous Bouquet Conformation Could Be An Ancient Fea...supporting
confidence: 66%
“…Previous reports in monotreme mammals (Daish et al, 2015) and some insects (Viera et al, 2017) have indicated that γH2AX is not necessarily a marker of DNA damage during prophase I. Our own observations indicate that γH2AX is not detected during prophase I in some reptiles (Marín-Gual et al, 2022a) (Page, unpublished). Therefore, is seems that some aspects of DNA damage signaling during meiosis in mammals and other vertebrates are yet to be properly characterized.…”
Section: Induction Of Dsbs and Synapsis Initiation And Progressionmentioning
confidence: 50%
See 1 more Smart Citation
“…Thus, the synapsis pattern of homologous chromosomes seems to be conditioned by the way DNA damage is produced during prophase I. The pattern observed in T. elegans and D. gliroides seems to be ancestral, and even shared by other non-mammalian vertebrates (Blokhina et al, 2019;Marín-Gual et al, 2022a). Finally, we highlight the possibility that a part of the DNA damage occurring in T. elegans and D. gliroides was not accompanied by H2AX phosphorylation.…”
Section: Induction Of Dsbs and Synapsis Initiation And Progressionmentioning
confidence: 64%
“…The excised testicular tissue (from September) was cut into 5 mm square blocks and fixed with 4% paraformaldehyde for 48 h. After alcohol dehydration, xylene clearing, and paraffin treatment, the paraffin-embedded tissues were sectioned at a thickness of 6 μm. After staining with hematoxylin and eosin (H&E), According to morphological characteristics of cytoarchitecture, spermatogenic cell types were judged ( Zhang et al 2008 , Marín-Gual et al 2022 ). The changes of spermatogenic cell assemblages in spermatogenic epithelium were compared in different seasons.…”
Section: Methodsmentioning
confidence: 99%